A new phreatic catfish of the genus Phreatobius Goeldi 1905 from groundwaters of the Iténez River, Bolivia (Siluriformes: Heptapteridae) - Fernandez, Luis; Saucedo, Lisandro J.; Carvajal-Vallejos, Fernando M.; Schaefer, Scott A. (Zootaxa, 2007)
Phreatobius sanguijuela, new species, is described from an artificial well located within the Río Paraguá drainage, a tributary of the Río Iténez, Bolivia. The new species is distinguished from its sole congener, P. cisternarum, by the absence of eyes, presence of 25–34 (versus 42–50) dorsal procurrent caudal-fin rays, 14–16 (versus 22–26) ventral procurrent caudal-fin rays, and 45–46 (versus 54–59) vertebrae. Both Phreatobius species are phreatic and known only from artificial wells penetrating near-surface aquifers of the Amazon River basin. Material of the new species represents the first records of Phreatobius from the upper Amazon, some 2000 km from reported locations of P. cisternarum near the Amazon River mouth. Phreatobius can be readily distinguished among siluriforms by the following combination of characters: dorsal and ventral procurrent caudal-fin rays extended rostrally, continuous with anal fin ventrally; caudal fin round; anal-fin rays unbranched; mouth prognathous, with jaws displaced dorsally on head; adductor mandibulae muscle hypertrophied, covering most of skull and posteriorly inserting onto first neural spine; first pectoral-fin ray soft, not spinous; bright red in life. This species is under severe threat from overexploitation by local people, who routinely capture and destroy it on the presumption that it represents a dangerous parasite.